2021
DOI: 10.1080/1828051x.2021.1928557
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potential of marine and freshwater algae as dietary supplements for growing rabbits

Abstract: The aim of this study was to investigate the effect of including marine and freshwater algae in rabbit diets on their performance, digestibility, carcass characteristics, and blood metabolites. One hundred growing male rabbits, aged 30 d and weighing 783.5 ± 2.01 g initial body weight, were randomly assigned to five treatment groups (n ¼ 20 rabbits). Five comparable dietary groups were formulated as follows: the control diet was a basal diet without aquatic plants inclusion, while the diets for the other four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Abu Hafsa et al [ 5 ], on laying quails, and Rizk et al [ 31 ] on laying hens found that the dietary inclusion of marine seaweeds improved their performance. According to Abu Hafsa et al [ 32 ], the growth performance improved significantly in rabbits fed 4% marine seaweeds. Adding seaweed to bird diets improved growth and health, as well as improving intestinal microflora [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abu Hafsa et al [ 5 ], on laying quails, and Rizk et al [ 31 ] on laying hens found that the dietary inclusion of marine seaweeds improved their performance. According to Abu Hafsa et al [ 32 ], the growth performance improved significantly in rabbits fed 4% marine seaweeds. Adding seaweed to bird diets improved growth and health, as well as improving intestinal microflora [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Balasubramanian et al [ 36 ] showed that broilers fed red seaweed-supplemented diets exhibited improved nutrient digestibility. The total digestible nutrients increased significantly in rabbits fed 4% marine seaweed, according to Abu Hafsa et al [ 32 ]. The current study revealed that growing Japanese quails fed S. siliquastrum performed as good as, or better than, quails fed a control diet.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content varies among groups, with red algae having the highest percentage (up to 47%) and brown algae the lowest (5–15%), and it is generally of very good quality in all types due to the high content of essential amino acids [ 69 ]. Seaweeds are a rich source of minerals, as they contain high levels of potassium, sodium and calcium, as well as iron, zinc, iodine, manganese, copper, cobalt and selenium [ 63 , 71 , 72 ] and also high levels of vitamins, especially vitamins A, C and E and the B group vitamins (B1, B2 and B12) [ 71 , 73 ]. Seaweeds also contain large amounts of PUFAs, particularly omega-3 and omega-6, which are present in a balanced ratio [ 69 , 71 , 72 ].…”
Section: Seaweed and Gut Healthmentioning
confidence: 99%
“…Seaweeds are a rich source of minerals, as they contain high levels of potassium, sodium and calcium, as well as iron, zinc, iodine, manganese, copper, cobalt and selenium [ 63 , 71 , 72 ] and also high levels of vitamins, especially vitamins A, C and E and the B group vitamins (B1, B2 and B12) [ 71 , 73 ]. Seaweeds also contain large amounts of PUFAs, particularly omega-3 and omega-6, which are present in a balanced ratio [ 69 , 71 , 72 ]. They are also rich in polyphenolic compounds (such as flavonoids and tannins), which act as strong antioxidants [ 69 , 70 , 71 , 73 ].…”
Section: Seaweed and Gut Healthmentioning
confidence: 99%
See 1 more Smart Citation